A Place to Rest Your (Burnt) Bones? Mortuary Houses in Early Anglo-Saxon England. Issue 1 (2nd January 2018) - Meyers Emery, Kathryn; Williams, Howard
Abstract : This article presents a fresh interpretation of square and rectangular mortuary structures found in association with deposits of cremated material and cremation burials in a range of early Anglo-Saxon (fifth-/sixth-century AD) cemeteries across southern and eastern England. Responding to a recent argument that they could be traces of pyre structures, a range of ethnographic analogies are drawn upon, and the full-range of archaeological evidence is synthesized, to re-affirm and extend their interpretation as unburned mortuary structures. Three interleaving significances are proposed: (i) demarcating the burial place of specific individuals or groups from the rest of the cemetery population, (ii) operating as 'columbaria' for the above-ground storage of the cremated dead  (i.e. not just to demarcate cremation burials), and (iii) providing key nodes of commemoration between funerals as the structures were built, used, repaired and eventually decayed within cemeteries. The article proposes that timber 'mortuary houses' reveal that groups in early Anglo-Saxon England perceived their cemeteries in relation to contemporary settlement architectures, with some groups constructing and maintaining miniaturized canopied buildings to store and display the cremated remains of the dead.